INVESTIGATING THE TREND OF EARLY MARRIAGE - Pangestu, Rizki; Ayu, Rizqa Febry (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2020)
Along with the development of increasingly modern times, there is a growing trend of asking for marriage. Many of them are mired in this young marriage tren’s problematics for various reasons, both positive and negative. Being too young does not become an obstacle to getting married. Even though marriage is not just a physical matter, it must be viewed from mental readiness. This research focuses on the implications of the trend of youth marriage requests. This research uses a qualitative analysis descriptive-analytical method. The study results show that the trend of young marriage will impact these parties, on the other hand, to avoid adultery and not fall into promiscuity.